2017
DOI: 10.3144/expresspolymlett.2017.88
|View full text |Cite
|
Sign up to set email alerts
|

The curing behavior and properties of phthalonitrile resins using ionic liquids as a new class of curing agents

et al.

Abstract: Abstract. Binary blends composed of 1,3-bis (3,4-dicyanophenoxy) benzene (3BOCN) and ionic liquids (ILs) with different molecular structures were prepared. The curing behavior of these 3BOCN/ILs blends were studied by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and rheological analysis. The study suggested that the blends possessed a wide processing window and the structures of ILs (anion, cation and alkyl chain length at cation) had an effect on curing behavior. The 3BOCN/[EPy]BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Co‐curing of PN systems with different types of cross‐linking agents has provided tuning of material properties of the resulting composites 24 . Curing PNs with ionic liquids can improve their dielectric and long‐term oxidative stabilities, likely due to the ability of these additives to induce a higher degree of cross‐linking within the thermosets 29 . Experiments that co‐cured PNs with tetrafluoroborate‐ and hexafluorophosphate ‐containing imidazolium‐ and pyridinium‐based ILs demonstrated that the addition of boron‐containing anions yielded much higher curing rates than phosphorus anion chemistries, while pyridinium were more effective than imidazolium cations at cross‐linking PNs 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Co‐curing of PN systems with different types of cross‐linking agents has provided tuning of material properties of the resulting composites 24 . Curing PNs with ionic liquids can improve their dielectric and long‐term oxidative stabilities, likely due to the ability of these additives to induce a higher degree of cross‐linking within the thermosets 29 . Experiments that co‐cured PNs with tetrafluoroborate‐ and hexafluorophosphate ‐containing imidazolium‐ and pyridinium‐based ILs demonstrated that the addition of boron‐containing anions yielded much higher curing rates than phosphorus anion chemistries, while pyridinium were more effective than imidazolium cations at cross‐linking PNs 29 .…”
Section: Introductionmentioning
confidence: 99%
“…These high stable units contributed to phthalonitrile resin with outstanding thermal stabilities, high T g , good flame retardancy and high mechanical properties, which could be applied as advanced structural materials 20–22 . However, pure phthalocyanine also showed high melting points and slow curing reactions without curing agents 23 . In order to improve the problems of pure phthalonitrile resin, phthalonitrile containing benzoxazine (BA‐ph) was synthesized in our previous researches with low melting point, wide processing window and self‐catalysis properties 24 .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] However, pure phthalocyanine also showed high melting points and slow curing reactions without curing agents. 23 In order to improve the problems of pure phthalonitrile resin, phthalonitrile containing benzoxazine (BA-ph) was synthesized in our previous researches with low melting point, wide processing window and self-catalysis properties. 24 The properties like curing reactions, processing properties, thermal stabilities and their fiber reinforced composites were investigated.…”
mentioning
confidence: 99%
“…Consequently, several curing agents, including ionic liquid and metal complexes, have been developed to reduce the curing temperature of phthalonitrile. [8][9][10][11][12] Laskoski et al 8 designed a new curing system with Cu(II) acetylacetonate/p-toluenesulfonic acid as the curing agent, where the curing temperature of the phthalonitrile resin was observed to reduce to around 150 C as compared to the traditional aromatic diamine curing agent. Nonetheless, the glass transition temperature (T g ) of the resin was 205 C only at a curing temperature of 300 C. Zhao et al 9 employed melamine as the curing agent.…”
Section: Introductionmentioning
confidence: 99%